PERILAKU HIGIENE PENGOLAH MAKANAN BERDASARKAN PENGETAHUAN TENTANG HIGIENE MENGOLAH MAKANAN DALAM PENYELENGGARAAN MAKANAN DI PUSAT PENDIDIKAN DAN LATIHAN OLAHRAGA PELAJAR JAWA TENGAH - Suci Fatmawati; Ali Rosidi; Erma Handarsari (Universitas Muhammadiyah Semarang, 2013)
The implementation of food hygiene and healthy food into basic principles of operation of the institution. chef has an important role in the smooth running of the production process because workers are planners, implementers and managers in an organization of food. There are four (4) factors that allow the transmission of disease through the food hygienic behavior, sources of infectious disease, the presence of the media (food, drinks) and recipient-recipient. The purpose of this study was to determine hygiene behavior based on chef knowledge of food processing hygiene in food holding in Center For Education And Training In Sports Student Central Java. Type of study is a descriptive with cross-sectional method, in which the cause and effect variables were measured at the same time. The research sample is whole chef in Sports Education and Training Center Student Central Java that as many as 6 people. The results showed that 50% of respondents had a good knowledge and 50% medium category. Knowledge chef is good enough, but seen from the behavior of chef is still less attention to hygiene. This shows that there is no relationship between knowledge of food hygiene and hygiene behavior chef.